ANALISIS PENGARUH KUALITAS PELAYANAN TELLER TERHADAP KEPUASAN ANGGOTA PADA BMT POLIDANA POLITEKNIK NEGERI SEMARANG - Sunindyo, Aris (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
This study aims to examine the quality of teller service which consists of tangibles, reliability, responsiveness, assurance, and empathy of member satisfaction by saving at Baitul Maal Wat Tamwil (BMT) Polidana Semarang State Polytechnic. The data used are primary data in the form of questionnaires' distribution to BMT members. The data used are primary data which are distributed through questionnaires to BMT members. This study used 100 members of the BMT Polidana as a sample. The data analysis tool used multiple regression analysis with SPSS 21. The results showed that tangibles, reliability, responsiveness and assurance had a significant effect on member satisfaction in saving at BMT Polidana State Polytechnic Semarang while empathy (empathy) does not have a significant effect on member satisfaction in saving at BMT Polidana Semarang State Polytechnic